PENERAPAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) UNTUK PEMILIHAN LOKASI PENDAKIAN GUNUNG DI INDONESIA - Muhammad Damar Yulian Prakarsa; Endah Asmawati; Daniel Hary Prasetyo (Perpustakaan Universitas Surabaya, 2022)
Abstract–So far, climbers have had difficulty in assessing and comparing several criteria. Climbers only use feelings in comparing several criteria. With the existence of a system that is able to consider criteria, it is expected to help climbers in determining climbing destinations. This system uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. In addition, this system provides data that can be used to consider mountain destinations that are in accordance with the wishes of climbers. In this system there is some information that can be utilized or used by the user to find out the current conditions about the climbing location including details of the climbing location, booking information & climbing quota, weather information and mountain activity status. This system uses a web platform. Based on trials and evaluations that have been carried out, it can be concluded that this system can help users to provide information on what mountains are most suitable for their wishes. Keywords: topsis, mountain, climbing, web Abstrak–Selama ini para pendaki kesulitan dalam menilai dan membandingkan beberapa kriteria. Para pendaki hanya menggunakan perasaan dalam membandingkan beberapa kriteria. Dengan adanya sistem yang mampu mempertimbangkan kriteria maka diharapkan dapat membantu para pendaki dalam menentukan destinasi tempat pendakian. Sistem ini menggunakan metode Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Selain itu sistem ini menyediakan data-data yang dapat digunakan untuk mempertimbangkan tujuan gunung yang sesuai dengan keinginan pendaki. Pada sistem ini terdapat beberapa informasi yang dapat dimanfaatkan atau digunakan oleh user untuk mengetahui kondisi saat ini tentang lokasi pendakian antara lain detail lokasi pendakian, informasi booking & kuota pendakian, informasi cuaca dan status aktifitas gunung. Sistem ini menggunakan platform web. Berdasarkan uji coba dan evaluasi yang telah dilakukan maka dapat disimpulkan sistem ini dapat membantu pengguna untuk memberikan informasi gunung apa yang paling sesuai dengan keinginan. Kata Kunci: topsis, gunung, pendakian, web